Determination of gamma-ray self-attenuation correction in environmental samples by combining transmission measurements and Monte Carlo simulations. (July 2016) - Šoštarić, Marko; Babić, Dinko; Petrinec, Branko; Zgorelec, Željka
Abstract: We develop a simple and widely applicable method for determining the self-attenuation correction in gamma-ray spectrometry on environmental samples. The method relies on measurements of the transmission of photons over the matrices of a calibration standard and an analysed sample. Results of this experiment are used in subsequent Monte Carlo simulations in which we first determine the linear attenuation coefficients (μ) of the two matrices and then the self-attenuation correction for the analysed sample. The method is validated by reproducing, over a wide energy range, the literature data for the μ of water. We demonstrate the use of the method on a sample of sand, for which we find that the correction is considerable below ~400 keV, where many naturally occurring radionuclides emit gamma rays. At the lowest inspected energy (~60 keV), one measures an activity that is by a factor of ~1.8 smaller than its true value. Highlights: Gamma-ray spectrometry. Self-attenuation correction. Monte Carlo simulation. Linear attenuation coefficient.